Research on safety methods of airborne embedded software - Ya-hui LI; Ya-di ZHANG; Peng GUO (Tongxin xuebao)
By analyzed the process of development and running of airborne software with the standards of airworthiness and information security,the factors and threats related with airborne software safety were presented,and the security protected mechanisms based on embedded TMP and MILS software architecture were provided,which all support the research on safety of embedded software on aircrafts.